MENU GIZI SEIMBANG UNTUK PENCEGAHAN STUNTING PADA BALITA DI DESA KABUPATEN KUDUS - Fariza Yulia Kartika Sari; Septiani Septiani; Rizki Widyan Aisya; Atun Wigati (Universitas Muhammadiyah Kudus, 2023)
Stunting is a nutritional problem that is a major problem in Indonesia. The Ministry of Health provides health programs in dealing with the problem of stunting. One of the efforts made to prevent stunting is through nutrition education. The purpose of community service activities (PKM) is to improve the subject's attitudes and behavior regarding toddler nutrition and types of food for stunting prevention. The method used is community empowerment by providing nutrition education and cooking demonstrations to subjects in the villages of Ngembal Rejo and Purwosari, Kudus Regency. Subjects in this PKM are posyandu cadres and mothers who have toddlers. The education given to the subject is about toddler nutrition and types of food for stunting prevention. The results of education show that there is an increase in subject knowledge after being given education. Subjects from cadres are expected to become agents of behavior change in preventing stunting for toddlers. Meanwhile, the subject of mothers who have toddlers is expected to be able to change behavior in providing food to their toddlers.